Neuroprotective effect of fermented papaya preparation by activation of Nrf2 pathway in astrocytes. (16th March 2018) - Murakami, Shinki; Miyazaki, Ikuko; Asanuma, Masato
Abstract : Objectives : Nuclear factor erythroid 2-related factor (Nrf2) in astrocyte plays important roles in brain homeostasis. Fermented papaya preparation (FPP) has anti-oxidative, anti-inflammatory, immunoregulatory properties. The present study investigated the effects of FPP on activation of Nrf2 and release of Nrf2-regulated neuroprotective antioxidants and detoxifying molecules. Methods : Primary cultured astrocytes from rat embryos were treated with FPP for 6 or 24 hours. The expression levels of nuclear Nrf2 and cytoplasmic Nrf2-regulated molecules were determined by western blot analysis and immunohistochemistry. Glutathione levels were measured in cells and medium. Dopaminergic neurons were exposed 6-hydroxydopamine (6-OHDA) with/without pre-treatment with FPP astrocytes. Mice were treated orally with FPP for 2 weeks. Results : FPP increased nuclear translocation of Nrf2 in striatal astrocytes, induced up-regulation of NAD(P)H quinine oxidoreductase-1, glutathione-S transferase and hemeoxygenase-1, and increased glutathione level and the percentage of metallothionein-expressing astrocytes. Moreover, FPP suppressed 6-OHDA-induced dopaminergic neuronal loss in not only neuron-astrocyte mixed culture, but also neuron-rich cultures pre-treated with glial conditioned medium. Two-week oral treatment of mice with FPP resulted in Nrf2 activation and increase in glutathione level in striatum. Discussion : The results indicated that FPP enhances the anti-oxidative capacity through activation of Nrf2 in astrocytes, suggesting it may provide neuroprotection in oxidative stress-related neurodegenerative diseases.